1997
DOI: 10.1088/0954-3899/23/6/011
|View full text |Cite
|
Sign up to set email alerts
|

First identification of high-spin states in Ta

Abstract: The yrast band in 166 Ta at high-spin states is established for the first time through the 141 Pr( 28 Si,3n) 166 Ta reaction at a beam energy of 127 MeV. Excitation function, residual radioactivity, and x-γ , γ -γ coincidences were measured. Signature inversion features of 166 Ta and neighbouring isotones are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Although Ref. [8] suggested that the 148-keV line decaying from the 11 − state is an in-band E2 transition, our normalized angular-correlation ratio of 0.63(6) is consistent with the transition being dipole ( I = 1) in nature. Thus, the 148-keV γ ray presumably feeds an I = 10 level, as drawn in Fig.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Although Ref. [8] suggested that the 148-keV line decaying from the 11 − state is an in-band E2 transition, our normalized angular-correlation ratio of 0.63(6) is consistent with the transition being dipole ( I = 1) in nature. Thus, the 148-keV γ ray presumably feeds an I = 10 level, as drawn in Fig.…”
supporting
confidence: 74%
“…Hild et al [7] investigated the feeding of 166 Ta levels from electron-capture decay of 166 W. A (2) + spin-parity assignment was proposed for the ground state, and four low-spin levels were identified. Zheng et al [8] more recently observed a single rotational band that was assigned to 166 Ta based on x-γ coincidences and on an excitation function. This structure is presented in the level scheme of Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations